2019
DOI: 10.1161/atvbaha.119.312005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, Obesity, and Diabetes Mellitus

Abstract: Obesity and diabetes remain leading causes of reduced health span and life span throughout the world. Hence, it is not surprising that these areas are at the center of highly active areas of research. The identification of novel mechanisms underlying these metabolic disorders sets the stage for uncovering new potential therapeutic strategies. In this issue of Highlights in Arteriosclerosis, Thrombosis and Vascular Biology, we review recently published papers in the journal that add to our understanding of caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…DM develops in obese and non-obese individuals when b-cell dysfunction manifests, resulting in a reduction in insulin secretion and an exacerbation of the abnormal glucose and lipid metabolism. 20,21 Pearson correlation analysis showed that HOMA-IR positively correlated with SBP, DBP, FPG, FINS, FFA, and TG in the T2DM-N group, indicating that HOMA-IR and IR increase with increases in all these parameters in patients with T2DM but no obesity. In addition, multiple linear regression analysis showed that HOMA-IR increased alongside FFA, TG, and SBP after correcting for FPG, FINS, age, BMI, DBP, fasting C-peptide, TCHO, HDLcholesterol, LDL-cholesterol and other factors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…DM develops in obese and non-obese individuals when b-cell dysfunction manifests, resulting in a reduction in insulin secretion and an exacerbation of the abnormal glucose and lipid metabolism. 20,21 Pearson correlation analysis showed that HOMA-IR positively correlated with SBP, DBP, FPG, FINS, FFA, and TG in the T2DM-N group, indicating that HOMA-IR and IR increase with increases in all these parameters in patients with T2DM but no obesity. In addition, multiple linear regression analysis showed that HOMA-IR increased alongside FFA, TG, and SBP after correcting for FPG, FINS, age, BMI, DBP, fasting C-peptide, TCHO, HDLcholesterol, LDL-cholesterol and other factors.…”
Section: Discussionmentioning
confidence: 93%
“…DM develops in obese and non-obese individuals when β-cell dysfunction manifests, resulting in a reduction in insulin secretion and an exacerbation of the abnormal glucose and lipid metabolism. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Immune cells are important factors in the regulation of adipose tissue function, and the dysfunction of adipose tissue caused by the imbalance of immune homeostasis is an important pathological and physiological mechanism of obesity. 5 Therefore, we hypothesized that obesity, T2DM and AITDs might share some common pathways. There is also further work we will do to explore how thyroid autoimmunity affects obesity and visceral obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that microvascular dysfunction is one of the key underlying mechanisms that is common in T2DM and began before the onset of T2DM (25). Microvessels are involved in the regulation of many brain functions and are mainly driven by a combination of factors such as high blood sugar, obesity, insulin resistance, and hypertension (26,27). A growing body of research has confirmed that diabetes-related microvascular dysfunction is associated with a higher risk of stroke, cognitive dysfunction, and depression.…”
Section: Discussionmentioning
confidence: 99%